Suscetibilidade in vitro de Malassezia pachydermatis frente a agentes antifúngicos e frações de óleos essenciais - Schlemmer, Karine Bizzi (2014)
The yeast Malassezia pachydermatis belongs to the normal microbiota of animals, and is usually implicated as responsible for otitis media and recently by various forms of dermatitis, mainly in dogs. This study aimed to evaluate the in vitro susceptibility of 26 M. pachydermatis isolates against the antifungals fluconazole, itraconazole, ketoconazole, clotrimazole, miconazole, terbinafine and nystatin, and to the combinations of these with thymol, carvacrol and cinnamaldehyde by the checkerboard method, based on document M27-A3. The activity of itraconazol, ketoconazole and clotrimazole against 20 isolates of M. pachydermatis, through simultaneous and sequential exposure of these agents, was also evaluated by the disk-diffusion technique. The minimum inhibitory concentration (MIC) for fluconazole ranged from 1-64 μg/mL, itraconazole 0.01-1 μg/mL, ketoconazole 0.01-0.5 μg/mL, clotrimazole 0.5-32 μg/mL, miconazole 2-32 μg/mL, terbinafine 0.12-32 μg/mL and nystatin 16-64 μg/mL. High rates of synergism were observed in the combinations of nystatin + thymol (88.46%), nystatin + carvacrol (88.46%), nystatin + cinnamaldehyde (73.07%), clotrimazole + thymol (69.23%), clotrimazole + carvacrol (69.23%), miconazole + thymol (65.38%), miconazole + carvacrol (76.92%) and miconazole + cinnamaldehyde (65.38%). However, high rates of indifference were observed in the combinations of fluconazole + thymol (53.84%), carvacrol + fluconazole (46.15%), fluconazole + cinnamaldehyde (65.38%), thymol + itraconazole (61.53%), carvacrol + itraconazole (69.23%), itraconazole + cinnamaldehyde (65.38%), terbinafine + thymol (73.07%), terbinafine + carvacrol (65.38%), terbinafine + cinnamaldehyde (73.07%) and clotrimazole + cinnamaldehyde (61.53%). Ketoconazole combined with thymol, carvacrol and cinnamaldehyde had the highest rates of antagonism (42.3%). The prior exposure of M. pachydermatis to itraconazole resulted in a reduction of the inhibition halo when compared with itraconazole and ketoconazole used simultaneously (p <0.01). Moreover, prior exposure of clotrimazole significantly increased the zone of inhibition (p <0.001) when compared to the simultaneous exposure of itraconazole and clotrimazole. The most significant associations deserve in vivo evaluation in order to verify their potential in the treatment of infections caused by M. pachydermatis.